Application of Nuclear Techniques to the Investigation of the Oxidation Behavior of Ion-Implanted Steels - Noli, F.; Misaelides, P. (HNPS Advances in Nuclear Physics, 2019)
The oxidation behavior of ion-implanted steel samples in air, using Nuclear Reaction Analysis (NRA) and Rutherford Backscattering Spectroscopy (RBS) techniques. Austenitic stainless steel AISI 321 (Fe/Crl8/Ni8/Mn2/Ti) samples implanted with magnesium-, aluminum- and zirconium-ions (implantation energy 40 keV, dose: 1-1017 to 2-1017 ions/cm2) were oxidized in air in the temperature region 450-650 °C for several periods of time. The above implants were selected on the basis of the affinity to oxygen, as well as their ability to form protective oxides as MgO, AI2O3, Zr02 in order to improve the oxidation resistance of steel. The determination of the oxygen concentration and depth-profiles was performed by means of the 160(d, p)170 nuclear reaction. Rutherford Backscattering Spectroscopy was applied to investigate the near-surface layers and to determine the depth profiles of the implanted ions. The determination of the aluminum concentration and the depth distribution of the Al-ions was performed using the resonance at 992 keV of the 27Al(p, 7)28Si nuclear reaction whereas the concentration and the depth distribution of the Mg-ions by the means of the 24Mg(o;, p)27Al reaction. The excitation function of the 24Mg(a:, p)27Al nuclear reaction was studied in the energy region 4600-5000 keV and absolute cross section data allowing the determination of the Mg-profile were determined for this purpose.